Development And Utilization Of AI In Creating Islamic Picture Stories At Rumah Kreatif Wadas Kelir Foundation Purwokerto - Bastian, Abda Billah Faza Muhammadkan; Mandalika, Rafli Arya; Nursa'adah, Salma (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The study aims to develop and utilize artificial intelligence (AI) to create Islamic illustrated stories at the Wadas Kelir Creative House Foundation in Purwokerto, Central Java Province. This research employs the ADDIE model as the framework for research and development. It is a type of Research and Development (R&D) focused on developing illustrated story media modules using the artificial intelligence tool DALL-E. The study was conducted at the Wadas Kelir Creative House Foundation in Purwokerto during August-September 2023, with data collection techniques including documentation and questionnaires. The results indicate that the development of Islamic illustrated story modules using DALL-E is highly effective in addressing the challenges faced by students and teachers in creating illustrated stories. The use of artificial intelligence simplifies teacher to process of producing images without requiring expertise in illustration software. The module covers an introduction to Islamic stories and DALL-E, steps for creating Islamic story media with DALL-E, editing and adjusting images, and compiling stories.